2006
DOI: 10.1080/09593332708618755
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cu and Zn Extractable Foliar Contents and BCR Sequential Extraction in Soil Treated with Organic Amendments

Abstract: The application of organic wastes to soils, such as municipal solid waste compost (MSWC) or treated urban sewage sludge (USS) is a current practice for maintaining soil organic matter, reclaiming degraded soils and supplying plant nutrients. Since USS and MSWC may contain organic contaminants, heavy metals or pathogens, this practice represents a potential problem to the environment. In the case of heavy metals both bioavailability and toxicity seems to be critically dependent on the chemical form of the eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The authors concluded that neither single nor sequential extractions provided a good prediction of metal bioavailability. Pedra et al 268 on the other hand concluded that both total and extractable metal concentrations gave adequate predictions of plant uptake.…”
Section: Interpretation Of Datamentioning
confidence: 99%
“…The authors concluded that neither single nor sequential extractions provided a good prediction of metal bioavailability. Pedra et al 268 on the other hand concluded that both total and extractable metal concentrations gave adequate predictions of plant uptake.…”
Section: Interpretation Of Datamentioning
confidence: 99%
“…In addition to chelators, composts have also been added in soils to assist phytoremediation. Their effects on properties of clay soils [12][13][14] as well as on plants growth [15,16] have both been examined. Compost-assisted phytoextraction in contaminated soils that are inimical to vegetation such as barren soils and mine tailings has also been conducted.…”
Section: Introductionmentioning
confidence: 99%